UMKM Pembinaan Usaha Mikro Kecil Dan Menengah Menggunakan Google My Business - JPKM UPB (Jurnal Pengabdian Barelang, 2019)
Micro, Small and Medium Enterprises are growing rapidly in recent years. This activity is a government effort to improve the economy of its people. This is not wasted by the community, especially those in the city of Batam. Many home-based businesses have emerged that are varied and do not miss using existing technology. One of them is using Facebook and Instagram applications. On Facebook, there are many online buying and selling forums. On Instagram it is the same. Many accounts post merchandise with photo or video media. But there are also other types of applications that can be utilized, namely Google My Business. This application is a feature developed by Google to move business towards the world of digital technology and digital markets. On Google My Business, all of these things already exist, one package all when we have registered with the application. However, the use of this application made by Google is not well known by the public, especially in MSMEs. Therefore proper coaching needs to be done so that the use of this google application can be utilized to the maximum extent possible and of course also brings more benefits as well.